Improving The Skills Of Writing Advertising Texts For Class VIII—A Students Of Smpn 16 Mandai Through The Picture And Picture Method - Melianti Melianti; Mayong Mayong; Azis Azis (SOCIETIES: Journal of Social Sciences and Humanities, 2022)
Abstract. Merlianti 2022. “Improving the Skills of Writing Advertising Texts for Class VIII-A Students of SMPN 16 Mandai Through the Picture and Picture Method". Thesis, Study Program of Indonesian Language and Literature Education, Department of Indonesian Language and Literature, Faculty of Language and Letters, Makassar State University. (Supervised by Mayong and Azis)This study aims to determine the improvement of students' advertising text writing skills using the picture and picture method. The problem that is found in the implementation of this research in general is the lack of skills of class VIII-A students of SMPN 16 Mandai in learning to write advertising texts. This type of research is classroom action research using research procedures with this through the stages which include: planning, implementing actions, observing and reflecting. The data of this research are in the form of process data and learning outcomes of writing advertisement text for class VIII A SMPN 16 Mandai.The results of this study indicate that there is an increase in student learning activities from cycle I to cycle II, namely the increase in the number of students in listening to the teacher's explanation, asking questions and answering questions, learning outcomes have also increased which can be proven from the results of the first cycle stage, which obtained a score of 570 and in cycle II 677 So that the application of the picture and picture method can increase the frequency of activity and activities by meeting the KKM standards. So that the teaching and learning process is in accordance with the observations of students during the implementation of class actions, it is enough for two cycles.Keywords: Improvement, Writing Ad Text, Picture And Picture Method